2018
DOI: 10.1016/j.heliyon.2018.e00580
|View full text |Cite
|
Sign up to set email alerts
|

Bouldering psychotherapy reduces depressive symptoms even when general physical activity is controlled for: A randomized controlled trial

Abstract: BackgroundBouldering psychotherapy (BPT) combines psychotherapeutic elements with physical activity (PA). It might be effective for reducing symptoms of depression, but so far, no study has assessed individuals' levels of PA to control for whether positive effects on depression can also be found when adjusting for participants' levels of PA. This is important because PA itself has been proven effective in reducing depression and therefore might be an important variable to account for – especially in therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 51 publications
4
72
0
Order By: Relevance
“…As we expected, depressive symptoms were effectively reduced in both the bouldering therapy group and the exercise group during the ten-week intervention period. These results are in accordance with previous studies on the antidepressant effects of physical exercise [8] and also parallel previous findings by our work group on the benefits of psychotherapeutic bouldering in treating depressive symptoms [35,36]. What has not been shown before and therefore represents new insights into the relation between physical activity and depression is the finding that the effect of the BPT seems to go even further than the effect of only physical activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As we expected, depressive symptoms were effectively reduced in both the bouldering therapy group and the exercise group during the ten-week intervention period. These results are in accordance with previous studies on the antidepressant effects of physical exercise [8] and also parallel previous findings by our work group on the benefits of psychotherapeutic bouldering in treating depressive symptoms [35,36]. What has not been shown before and therefore represents new insights into the relation between physical activity and depression is the finding that the effect of the BPT seems to go even further than the effect of only physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…Simultaneously, in the confounder-adjusted regression analysis, group allocation (BPT vs. EP) emerged as the only relevant predictor of the post-intervention depression score measured with the MADRS. These findings underpin and augment the previous results of our work group's pilot trial [36], which suggested therapeutic effects of a bouldering psychotherapy intervention on depressive symptoms even when general activity was controlled for. With a moderate effect size (Cohen's d) of 0.55 for the MADRS, the effect of the BPT intervention applied in the current study was weaker than that of the BPT in the pilot study (Cohen's d = 0.77).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…If social support is provided then aerobic exercise can cause substantial improvements in the depression level. The effect of both psychotherapeutic and physical exercise on the depression was also studied [19]. patients [27].…”
Section: Lifestyle Medicinementioning
confidence: 99%
“…Different health outcomes were assessed with standardised psychological self-report questionnaires before and after the eight-week intervention period as well as 16 weeks after the end of the therapy. Participants in the intervention group reported a significant reduction in depressive symptoms compared with the control group, even when other types of physical activity was controlled for [33, 34]. With an effect size (Cohen’s d ) of 0.77 (moderate effect) the effect of the bouldering intervention on depressive symptoms was comparable to other short-term group therapies [35] and to physical activity (see above).…”
Section: Introductionmentioning
confidence: 99%